Integrated lean logistics - warehousing model to reduce lead time in an SME of food sector: a research in Peru - Gamio Valdivia, Karina Guiuliana (2023)
The food industry represented 3.2% of the Gross Domestic Product (GDP) in Peru in 2019, in addition to presenting high employability since the sector contained 7.4% of the Economically Active Population (EAP). Due to the global crisis of COVID 19 in 2020, this sector has been affected, consequently the GDP of the restaurant and accommodation sector fell by 50.2% compared to the previous year. Therefore, the strengthening of this industry is considered crucial. Being one of the most critical links in the management of the material supply chain, this problem translates into late delivery of orders to your customers, which would generate large monetary losses and a bad reputation. In this sense, the present investigation proposes a comprehensive improvement model based on the combination of tools such as the 5S of the raw material under a multi-criteria ABC approach, FEFO, MRP, Forecasting and BPM whose objective is to reduce lead time. The model was validated through a simulation in Arena 16.1, where a reduction in delivery time and in the frequency of extra purchases was obtained by 7.2% and 50%.